2017
DOI: 10.1038/s41598-017-03007-1
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a planar direct-current glow discharge in atmospheric pressure air using rod array electrode

Abstract: Scaling up atmospheric pressure glow discharge to large volume is desirable for low-temperature plasma applications. In this paper, an approach to generate a glow discharge in a planar shape with a fairly large volume is proposed in atmospheric pressure air through utilizing a direct-current excited rod array electrode. The planar discharge with a wide gap originates from three discrete discharges with a narrow gap. Based on electrical method and optical emission spectroscopy, it is found that gap voltage incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Considering that this continuum emission was not observed in the case of 1.24 mA discharge, it could be concluded that it comes from the white area of the plasma (Figure 4f,h), which does not appear in the case of low current (Figure 4b,d). Taking into account the higher power of the discharge, white continuum emission could be attributed to the overlapping of abundant energy levels for the diatomic molecule (N 2 (B-A)) and black body radiation [16], [47], [48].…”
Section: Overview Optical Emission Spectramentioning
confidence: 99%
“…Considering that this continuum emission was not observed in the case of 1.24 mA discharge, it could be concluded that it comes from the white area of the plasma (Figure 4f,h), which does not appear in the case of low current (Figure 4b,d). Taking into account the higher power of the discharge, white continuum emission could be attributed to the overlapping of abundant energy levels for the diatomic molecule (N 2 (B-A)) and black body radiation [16], [47], [48].…”
Section: Overview Optical Emission Spectramentioning
confidence: 99%
“…To prevent the unwanted transition of glow to arc discharge, a dielectric barrier that can easily control the current during discharge is commonly used, thus resulting in AC discharge [ 19 , 20 , 21 , 22 , 23 ]. When generating a DC discharge, it is common to expose the powered electrode to the discharge space, include a proper ballast resistor in the circuit to control the current, and ground the counter electrode [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. However, even when the tip of the tungsten wire electrode of the newly designed AP-plasma reactor was exposed to the discharge space, a ballast resistor was not needed because the AC voltage was applied at a frequency of about 30 kHz, and the glow discharge occurred in a single electrode structure without a ground electrode.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, glow mode is desirable in a wide range of applications where there is a need for uniform treatment, such as biomedical applications 2 , surface modification 4,5 , and gas conversion 6 . Although glow discharge is formed simply under low pressure, on an industrial scale, the use of atmospheric pressure plasma is superior to the use of low pressure plasma due to the lack of vacuum equipment 7 . Organization of glow mode in DBD at atmospheric pressure with electronegative gases such as air, in which recombination of electrons is not negligible, is a challenging problem due to the week memory effect [2][3] .…”
Section: Introductionmentioning
confidence: 99%
“…Organization of glow mode in DBD at atmospheric pressure with electronegative gases such as air, in which recombination of electrons is not negligible, is a challenging problem due to the week memory effect [2][3] . The most of attempts to create a glow discharge at atmospheric pressure led to the creation of this discharge under limited conditions, such as the creation of a glow discharge under very small millimeter gaps 4,7 and using noble gases, such as helium and neon [8][9][10][11] to create a large gap, which on an industrial scale is not economically feasible. creating a discharge in ambient air is more effective due to the presence of active species of oxygen and nitrogen (ROS and RNS), which play a fundamental role in many plasma applications 12 .…”
Section: Introductionmentioning
confidence: 99%